Faktor-faktor Penyebab Pernikahan di Usia Dini serta Upaya Penanganannya (Studi pada Kantor KUA Medan Denai) - Safria Andy; Putri Balqis Fahira Santoso; Taufik Hidayat Pasaribu (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
At present the phenomena and problems that still occur in one of the sub-districts in Medan City, to be precise in Medan Denai District, are marriage at an early age. The problem of early marriage or often called underage marriage is no longer a new phenomenon in an area. Early marriage is a very serious problem and interpersonal communication is aware of it. The aim of this research is to prevent marriage at an early age in the community, especially in Medan Denai District. The research was conducted using qualitative methods presented in descriptive form. Data collection was carried out through direct observation and interviews with informants in the study, namely some people who married at an early age, religious leaders, heads of KUA and staff. The results of the study show that the factors that cause early marriage are due to economic factors, education, self-desire, parents' wishes, MBA (marriged by acident) factors, media, customs/culture. Efforts made by the Office of Religious Affairs are conducting outreach regarding the age limit for marriage, reproductive health, and collaboration between the Office of Religious Affairs and the local community. It is hoped that knowing the causal factors and the solutions that have been given will prevent cases of marriage at an early age.